Pengaruh Globalisasi Terhadap Perkembangan Hak Asasi Manusia Bidang Ekonomi, Sosial, Budaya (HESB) Di Indonesia - Erlina B (PRANATA HUKUM, 2011)
This study discussed the influence of globalization toward the development of human rights in economic, social and culture in Indonesia. The influence of globalization in Indonesia is very strong, there is shift of values and norms which underlie and control human rights in several different countries, because the limit of those values began to disappear, there are values which survive and there are values which shift. The right solution is to build law based on Pancasila values in legislation organic and to implement Pancasila in the state and nation âs lift correctly.